Mycorrhizal mycelial respiration: A substantial component of soil respired CO2. (December 2021) - Han, Mengguang; Feng, Jiguang; Chen, Ying; Sun, Lijuan; Fu, Liangchen; Zhu, Biao
Abstract: Mycorrhizal fungi constitute a considerable sink for plant photo-assimilates, yet poor knowledge about mycorrhizal mycelial respiration (RMyc ) hinders the quantification of its role in belowground carbon cycling. We synthesized available field data of RMyc, and found that RMyc contributed 15% of soil respiration and 38% of autotrophic respiration (including RMyc and root respiration, RRoot ). We observed no significant differences of RMyc between ectomycorrhiza and arbuscular mycorrhiza dominated ecosystems. Both RMyc /RRoot and RMyc /(RRoot  + RMyc ) significantly decreased with increasing RRoot, and correlated with absolute latitude, mean annual temperature and precipitation. Collectively, RMyc is a substantial component of soil respiration and exhibits divergent geographical pattern with that of RRoot, and should be considered separately in terrestrial carbon cycling models. Highlights: RMyc contributed 15% of soil respiration and 38% of autotrophic respiration. RMyc was similar between ECM and AM dominated ecosystems. Both RMyc /RRoot and RMyc /(RRoot  + RMyc ) decreased with increasing root respiration. Both RMyc /RRoot and RMyc /(RRoot  + RMyc ) increased with absolute latitude. MAT and MAP showed negative correlations with RMyc /RRoot and RMyc /(RRoot  + RMyc ).